Costa Rican Regulations To The Right To Work Of The Population With Disabilities, From A Human Rights Approach (Revista Rupturas, 2023)
The following article analyzes the main regulation related to the right to work that the population with disabilities has in Costa Rica, from a Human Rights Approach (HRA). This implies that the regulation is understood and observed from the fundamental categories of Human Rights (HHRR), in order to interpret from this perspective, the success and challenges of the regulation in reference to this right.
Keywords: Human Rights; Disability; Work; Laws